Bacteriome Identified by Next-Generation Sequencing in Saliva, Dental Plaque, and Tumor Tissue of Patients with Oral Squamous Cell Carcinoma (2021)
Oral squamous cell carcinoma (OSCC) is the sixth most common cancer in the world, and the bacterial microbiome has been considered a risk factor that could play an important role in carcinogenesis. Objective: A bacteriome study was performed by next-generation sequencing in dental plaque, saliva, and tumor samples of 10 OSCC patients and compared with bacteriome in dental plaque and saliva of 10 patients without OSCC. Methods: DNA was extracted from all samples and sequenced by Illumina technology MiSeq™. Bioinformatic analyzes were performed for evaluated sequence quality, alpha and beta diversity, bidirectional analysis of variance (p <0.05), and principal component analysis. After establishing bacterial profiles associated with each sample and population, intragroup and intergroup comparisons were carried out. For bacteria identification compatible with eubiosis and dysbiosis processes, a screening was performed based on the frequency of appearance in all patient samples with and without OSCC. Lastly, frequency, average, standard deviation, Chi-square, and Mann Whitney test were calculated. Results: Out of the identified 1,231 bacteria in the populations under study, 45 bacterial species were selected, of which 34 were compatible with eubiosis, and 11 were compatible with dysbiosis. Among the bacteria compatible with eubiosis were species of Lactobacillus and Streptococcus, Chromobacterium violaceum, Enterobacter asburiae, Mycobacterium chubuense, Mycoplasma penetrans, and Brachyspira intermedia. Among the species associated with dysbiosis,  Providencia stuartii, Capnocytophaga canimorsus, Legionella pneumophila, and Mycoplasma hominis were notable. Conclusion: Thirty-four bacterial species may be associated with eubiosis or healthy states and 11 bacterial species could be associated with dysbiosis or pathogenic state, OSCC.